Distance learning impact: Interaction, orientation, multimedia, cognitive engagement, learning performance - Yulhendri, Yulhendri; Antomi, Yudi; Sofya, Rani; Ritonga, Mentari; Rahmi, Yuri (International Journal of Innovative Research and Scientific Studies, 2025)
Students face challenges in literacy and autonomy in distance learning, particularly due to the lack of faculty control over their participation, which impacts their academic performance. This research aims to analyze the impact of multimedia use, online interaction, and cognitive engagement on students’ learning outcomes in Indonesia during the COVID-19 pandemic. Using the ex post facto method, data were collected from 588 students through multistage random sampling techniques and analyzed using Measurement Model Assessment and Structural Equation Modeling. The research results show that the use of multimedia in learning, active interaction between students and lecturers, as well as a clear learning orientation, enhance students’ cognitive engagement, which ultimately contributes to improved academic performance. Better interactions, such as discussions with lecturers and peers, as well as the use of data analysis tools, have been proven to enhance the effectiveness of learning. In addition, the use of multimedia in delivering materials and reviewing learning also has a positive impact on students’ understanding. This study contributes by identifying effective online learning strategies, including the use of the Zoom platform and multimedia tools, to enhance student engagement and learning outcomes.